TNF-308G > A Single Nucleotide Polymorphism Is Associated With Leprosy Among Brazilians: A Genetic Epidemiology Assessment, Meta-Analysis, and Functional Study - Cardoso, Cynthia C.; Pereira, Ana Carla; Brito-de-Souza, Vania N.; Duraes, Sandra M. B.; Ribeiro-Alves, Marcelo; Nery, Jose Augusto C.; Francio, Angela S.; Vanderborght, Patricia R.; Parelli, Francisco P. C. [UNESP]; Alter, Andrea; Salgado, Jorge Luis; Sampaio, Elizabeth P.; et al. (Oxford University Press, 2011)
Leprosy is an infectious disease caused by Mycobacterium leprae. Tumor necrosis factor (TNF) plays a key role in the host response. Some association studies have implicated the single nucleotide polymorphism TNF -308G > A in leprosy susceptibility, but these results are still controversial. We first conducted 4 association studies (2639 individuals) that showed a protective effect of the -308A allele (odds ratio [OR] = 0.77; P = .005). Next, results of a meta-analysis reinforced this association after inclusion of our new data (OR = 0.74; P = .04). Furthermore, a subgroup analysis including only Brazilian studies suggested that the association is specific to this population (OR = 0.63; P = .005). Finally, functional analyses using whole blood cultures showed that patients carrying the -308A allele produced higher TNF levels after lipopolysaccharide (LPS) (6 hours) and M. leprae (3 hours) stimulation. These results reinforce the association between TNF and leprosy and suggest the -308A allele as a marker of disease resistance, especially among Brazilians.